Mental Health Impact of Coronavirus Disease 2019 Pandemic on Children with Psychiatric Disorder - Duarte, Nuno (2022)
Introduction: The first full lockdown due to the coronavirus pandemic in Portugal started in March 2020 and sent home every child, only to return to school in September the same year. Children are thought to cope harder with this pandemic, but little is known about those already struggling with psychiatric conditions. Methods: We interviewed parents of 196 children in psychiatric follow-up in Clínica da Encarnação, a child psychiatry unit, Centro Hospitalar Universitário Lisboa Central, and reported their perception of the impact of the lockdown on the mental health of their children, as well as on their families. Results: The parents reported a slight deterioration of their children condition and symptomatology, particularly irritability and anxiety. We identified several important fragility factors such as female gender, lower school grade, higher daily screen time, lower housing quality, parental precarious job situation, parental psychiatric disorder, pharmacologic treatment, and shorter follow-up time. We also found some resilience factors such as coronavirus disease 2019 cases in the family and school failure, as well as male gender and shorter daily screen time. The  mparents who reported a deterioration of familial conflicts also reported a worse lockdown impact on their children psychiatric condition. Discussion: Our findings suggest a heterogeneous impact on these children’s psychiatric symptomatology. Efforts should be made towards prevention along with interventions. The fragility and resilience factors identified should help direct these interventions.